Surprises during intravitreal drug delivery—a report of three cases - Venkatesh, Pradeep; Chawla, Rohan; Shah, Bhavin; Garg, Sat Pal (Digital Journal of Ophthalmology, 2017)
We describe 3 cases with unusual events during and after intravitreal injection of dexamethasone intravitreal implants and bevacizumab. In case 1, delayed release of the safety stop of a dexamethasone intravitreal implant injector led to impaction and retinal break formation. Timely recognition and laser treatment prevented further retinal complications. In case 2, reinjection of a second dexamethasone intravitreal implant from the same site as the first injection was noted to dislodge the remnant of the previous implant from the vitreous base. In case 3, translucent floating particles were noted in the vitreous after intravitreal injection of bevacizumab from ampules procured from our dispensing pharmacy.